Evaluation of Braking Timing Sequence of Semi-Trailer Train Based on Fuzzy Analytic Hierarchy Process - Shiyuan Feng; Libin Zhang; Hongying Shan; Minghang Zhang (Applied Sciences, 2022)
A reasonable braking timing sequence plays an important role in the braking stability of a semi-trailer train, but there is still a lack of objective and comprehensive scientific evaluations of braking stability as shown by the braking timing sequence. Aiming at this problem, through the analysis of relevant regulations and standards at home and abroad, an evaluation index hierarchy model of the semi-trailer train braking timing sequence is constructed. The fuzzy analytic hierarchy process is used to determine the weight of the evaluation index of each level of the braking timing sequence, and a comprehensive evaluation is obtained. In order to determine the optimal braking timing sequence of the train during braking, a simulation model was established and simulated. Through the combination of index weight and simulation data, the model can provide a theoretical basis for the subsequent study of the optimal braking timing sequence of semi-trailer trains running under different working conditions.